The Influence Of The Economic Environment And Entrepreneurship Knowledge On Online Purchasing Decisions Of The Kemantrenrejo Community - Nunuk Indarti; Sapto Hadi Riono; Nundiah Zuhrohfi Immaroh (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the influence of the economic environment on online purchasing decisions in the community of Kemantrenrejo Village. The research method used was a quantitative survey by distributing questionnaires to 100 randomly selected respondents. Economic environment variables are measured through indicators of income, education level, and access to technology, while online purchasing decisions are measured through the frequency of purchases, the type of goods purchased, and the value of transactions. The results showed that income and access to technology had a significant influence on online purchasing decisions, while education levels did not show a significant influence. These findings indicate that the higher the income and the better the access to technology owned by the community, the greater their tendency to make online purchases. This research contributes to the understanding of consumer behavior in rural areas and can be a reference for the development of digital marketing strategies in the region.